Tuberculosis fatality rates in the city of Campinas - São Paulo, Brazil, from 2001 to 2009 - Oliveira,Helenice Bosco de (2019)
ABSTRACT: Introduction: The mortality rate among tuberculosis patients (TB fatality) has been attributed to irregular chemotherapy, delay in diagnosis, multidrug resistance, and HIV coinfection. Objective: To analyze TB fatality rates by sex, clinical presentation and HIV coinfection in Campinas, São Paulo, Brazil. Methods: Cohorts of residents in the city of Campinas who either died during treatment for tuberculosis or had the disease confirmed after death were divided into three intervals: 2001-2003, 2004-2006, and 2007-2009. Data were obtained from the database of the Tuberculosis Surveillance System of the University of Campinas, and notifications were gathered through TB-WEB Health São Paulo Secretary. Statistical significance was determined using a chi-square test, considering p < 0.05. Results: Between 2001 and 2009, 3,416 TB patients were diagnosed: 2,827 (82.8%) were new TB cases and 589 (17.2%) were retreatments. Between the first and second triennium, the number of new patients decreased by 18%, and 23% among retreatments. Between the second and third intervals, the reduction was 5% and 21%, respectively. General case fatality rate declined from 11.4% to 9.9% across intervals, and was most significant among patients that had previously abandoned treatment (17.3% to 5.1%). Fatality rates among patients coinfected with TB-AIDS were 2-3 times that of patients not infected with TB-AIDS throughout the intervals. Fatality between the first and third triennium among TB-AIDS co-infected patients declined (24.8% to 19.5%), while increasing slightly among non-AIDS TB patients (7.3% to 8%) during this period. Conclusion: Though mortality among TB-AIDS patients declined from 2001-2009, rates among non-AIDS TB remained stagnant. Improved TB diagnosis and treatment is needed to further decrease TB mortality in Campinas.